In-Flight Injuries Involving Children on Commercial Airline Flights. Issue 10 (October 2019) - Alves, Paulo M.; Nerwich, Neil; Rotta, Alexandre T.
Abstract : Background: More than 3 billion passengers are transported every year on commercial airline flights worldwide, many of whom are children. The incidence of in-flight medical events (IFMEs) affecting children is largely unknown. This study seeks to characterize pediatric IFMEs, with particular focus on in-flight injuries (IFIs). Methods: We reviewed the records of all IFMEs from January 2009 to January 2014 involving children treated in consultation with a ground-based medical support center providing medical support to commercial airlines. Results: Among 114 222 IFMEs, we identified 12 226 (10.7%) cases involving children. In-flight medical events commonly involved gastrointestinal (35.4%), infectious (20.3%), neurological (12.2%), allergic (8.6%), and respiratory (6.3%) conditions. In addition, 400 cases (3.3%) of IFMEs involved IFIs. Subjects who sustained IFIs were younger than those involved in other medical events (3 [1–8] vs 7 [3–14] y, respectively), and lap infants were overrepresented (35.8% of IFIs vs 15.9% of other medical events). Examples of IFIs included burns, contusions, and lacerations from falls in unrestrained lap infants; fallen objects from the overhead bin; and trauma to extremities by the service cart or aisle traffic. Conclusions: Pediatric IFIs are relatively infrequent given the total passenger traffic but are not negligible. Unrestrained lap children are prone to IFIs, particularly during meal service or turbulence, but not only then. Children occupying aisle seats are vulnerable to injury from fallen objects, aisle traffic, and burns from mishandled hot items. The possible protection from using in-flight child restraints might extend beyond takeoff and landing operations or during turbulence.